IMPLEMENTASI LINGKUNGAN BERSIH DAN SEHAT MELALUI PEMANFAATAN LUBANG BIOPORI SEBAGAI PUPUK ORGANIK DAN RESAPAN AIR DI DESA KAYANGAN, KECAMATAN KAYANGAN, KABUPATEN LOMBOK UTARA - Pramita, Rike Wahyu; Haqiqi, Afiyat Isna; Hidayati, Nurul; Dewi, Dhea Sukma; Hidayat, Pasya Rama; Arsyi, M.; manurak, Windilia Eo; Fahmi, M. Izzul; Aulia, Fadila Rizkina; Utami, Rizki (Universitas Mataram, 2024)
The 2024 KKN PMD-UNRAM program in Desa Kayangan, North Lombok, West Nusa Tenggara, focused on improving environmental quality through the implementation of biopore hole technology. Desa Kayangan, known for its fertile agricultural potential, faced significant challenges in organic waste management and waterlogging. The 2024 KKN PMD-UNRAM program initiated an innovative solution through the implementation of biopore hole technology. By actively involving the community, the program was able to significantly reduce organic waste volume, improve soil quality, and reduce the risk of waterlogging. Biopore holes not only serve as a medium for composting organic waste but also increase groundwater infiltration capacity. As a result, the program not only provides a technical solution but also promotes behavioral changes in the community towards more sustainable environmental management. The active participation of the community in the construction and maintenance of biopore holes is the key to the success of this program. This program proves that with the right approach and community participation, complex environmental problems can be addressed effectively and sustainably.